Celebrations of death the anthropology of mortuary ritual - Metcalf, Peter; Huntington, Richard 1945- (Cambridge University Press, 1991)
This revised edition of a cross-cultural study of rituals surrounding death has become a standard text in anthropology, sociology and religion. Part of its fascination is that in understanding other people's death rituals we are able to gain a better understanding of our own. The authors refer to a wide variety of examples, from different continents and epochs. They compare the great tombs of the Berawan of Borneo and the pyramids of Egypt, as well as the dramas of medieval French royal funerals and the burial alive of the Dinka 'masters of the spear' in the Sudan, and other rituals which at first sight seem to have little in common. Many of these cases are anthropological classics, but the authors place them in an alternative context, so as to shape a novel synthesis on the anthropology of death ritual. A fresh introduction reviews theoretical developments in the field since the book first appeared in 1979.